The Relationship Between Companies Characteristics and Key Audit Matters (KAM): A Case Study of ISSI Indexed Companies - Durohman, Hapid; Rahmah, Faatih; Manika, Quri Zahra (Review on Islamic Accounting, 2025)
The role of the audit profession and the implementation of new audit standards are aimed at improving the quality of audit reports and one of the recent improvements is the inclusion of Key Audit Matters (KAM) as a separate section in the auditor's report. This inclusion aims to enhance the communicative value of audit reports, providing users with greater transparency. This study aims to contribute to the current literature by determining the matters which should be included as KAMs and the factors affecting KAM disclosure. It also examines the relationship between the total number of KAMs, nominal of KAMs and firm level characteristics. This study employs descriptive quantitative approach which use secondary data from 385 companies listed on the Indonesian Stock Exchange (IDX) and indexed by ISSI. The research utilizes two methods, namely multiple linear regression, and logistic regression. The findings of this study reveal that the variables of complexity, financial performance, and financial indebtedness exert a significant influence on the total number of Key Audit Matters (KAMs). Additionally, the variables of opinion and financial performance significantly impact the nominal Key Audit Matters (KAMs).